Tree-ring-inferred glacier mass balance variation in southeastern Tibetan Plateau and its linkage with climate variability - Duan, J.; Wang, L.; Li, L.; Sun, Y. (Climate of the Past, 2013)
A large number of glaciers in the Tibetan Plateau (TP) have experienced wastage in recent decades. And the wastage is different from region to region, even from glacier to glacier. A better understanding of long-term glacier variations and their linkage with climate variability requires extending the presently observed records. Here we present the first tree-ring-based glacier mass balance (MB) reconstruction in the TP, performed at the Hailuogou Glacier in southeastern TP during 1868-2007. The reconstructed MB is characterized mainly by ablation over the past 140 yr, and typical melting periods occurred in 1910s-1920s, 1930s-1960s, 1970s-1980s, and the last 20 yr. After the 1900s, only a few short periods (i.e., 1920s-1930s, the 1960s and the late 1980s) were characterized by accumulation. These variations can be validated by the terminus retreat velocity of Hailuogou Glacier and the ice-core accumulation rate in Guliya and respond well to regional and Northern Hemisphere temperature anomaly. In addition, the reconstructed MB is significantly and negatively correlated with August-September all-India monsoon rainfall (AIR) (r(1871-2008) = -0.342, p < 0.0001). These results suggest that temperature variability is the dominant factor for the long-term MB variation at the Hailuogou Glacier. Indian summer monsoon precipitation does not affect the MB variation, yet the significant negative correlation between the MB and the AIR implies the positive effect of summer heating of the TP on Indian summer monsoon precipitation.